Characterization of chemically modified gold and silver clusters in gas phase. Issue 32 (31st July 2019) - Hirata, Keisuke; Tomihara, Ryohei; Kim, Kuenhee; Koyasu, Kiichirou; Tsukuda, Tatsuya
Abstract : This perspective summarizes our recent efforts in the application of gas-phase characterization methods to ligand-protected Au/Ag clusters chemically synthesized with atomic precision. Abstract : Atomically precise Au and Ag clusters protected by organic ligands can be viewed as chemically modified Au/Ag superatoms and have attracted interest as promising building units of functional materials and ideal platforms for studying the size-dependent evolution of structures and properties. Their structures, stability, and physicochemical properties have been characterized in solution and solid (or crystalline) phases by various methods conventionally used in materials science. However, novel and complementary information on their intrinsic stability and structures can be obtained by applying a variety of gas-phase methods, including mass spectrometry, ion mobility mass spectrometry, collision- or surface-induced dissociation mass spectrometry, photoelectron spectroscopy, and photodissociation mass spectrometry, to the chemically modified Au/Ag superatoms isolated in the gas phase. This perspective describes our recent efforts in the gas-phase studies on chemically synthesized Au/Ag superatoms.